2021
DOI: 10.21037/apm-21-1156
|View full text |Cite
|
Sign up to set email alerts
|

Oral adverse effects of CDK4/6 inhibitors among breast cancer patients: a systematic review and meta-analysis

Abstract: Background: Cyclin-dependent kinase (CDK) inhibitors are widely used to treat hormone receptor-positive (HR+) breast cancer due to their efficient performance in improving survival outcomes. Although the side effects of these agents on the hematological and gastrointestinal systems have attracted significant attention, the adverse effects that have direct impacts on patients' quality of life, such as stomatitis, have not been well explored to date.Methods: A systematic literature search was conducted in the Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Higher RRs were observed among patients receiving letrozole (8.50, 95% CI: 2.22–32.57) or palbociclib-containing regimens (2.44, 95% CI: 1.88–3.18). 40 …”
Section: Adverse Event Profile Of Cdk4/6 Inhibitorsmentioning
confidence: 99%
“…Higher RRs were observed among patients receiving letrozole (8.50, 95% CI: 2.22–32.57) or palbociclib-containing regimens (2.44, 95% CI: 1.88–3.18). 40 …”
Section: Adverse Event Profile Of Cdk4/6 Inhibitorsmentioning
confidence: 99%
“…Additionally, findings from a singular study (Cejuela et al, 2023) underscored diarrhea as a significant adverse reaction experienced by all patients, highlighting its clinical importance (Arbuckle et al, 2000). A meta-analysis regarding the risk of other side effects, such as stomatitis, demonstrated that especially palbociclib, among all CDK4/6i, could increase this risk impacting on patient adherence to the treatment (Long et al, 2021).…”
Section: Introductionmentioning
confidence: 99%